Mobile Bookstore (m-Bookstore) - Roslan, Aman Zenni (Universiti Teknologi Petronas, 2006)
Mobile technologies and computing are evolving and expanding each day, demanding and creating a much more ubiquitous computing environment. This research project proposes the development and implementation of the Mobile Bookstore - a mobile solution for bookstore businesses. This report presents the final research and study of the development of the Mobile Bookstore as a solution to the problem statements stated in the project proposal as well as in this report, which is considered as the main objective of the study. The Mobile Bookstore will address to the four problem statements, which are the geographical problems, the advancing mobile technologies, ubiquitous demands in computing and large bookstore information requests. These objectives help in answering the question to why this research is done and why would we need a mobile bookstore? With the mobile bookstore, companies can reach out to more customers, anywhere and everywhere using mobile devices. This concept allows for a more ubiquitous business and computing. Major bookstores need to compete and to be on top, implementing the latest technologies to serve its customers, and the mobile technology is one that should be taken advantage of. Browsing the large database of a bookstore can be time-consuming and difficult using expensive kiosks that come in limited numbers. A wireless environment can create wireless networks allowing those with mobile devices to browse through the bookstore database with ease. With this report, the basis for the research of this project will be underlined in detail, including the technologies, means, methods and study of recent researches related to the study. The result of this research project will be the software solution, a system (the Mobile Bookstore), which consists of two modules: the outdoor WAPbased module and the indoor Wireless Network module.